1992
DOI: 10.1038/bjc.1992.335
|View full text |Cite
|
Sign up to set email alerts
|

No effect of dose, hepatic function, or nutritional status on 5-FU clearance following continuous (5-day), 5-FU infusion

Abstract: Summary One hundred and eighty seven patients (155 males, 32 females) with histologically proven and previously untreated head and neck cancer were entered in the study. A total of 222 cycles of therapy were analyzed (cisplatin 100 mg m-2 on day I and 5-day continuous intravenous infusion of 5-FU 550-1069 mg m-2 day-', mean 875.5 mg m-2 day-'). Significant interpatient variability for various 5-FU pharmacokinetic parameters was observed including an almost ten-fold range in 5-FU clearance (5-FU Cl, ml min-m-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…CL 5FU of 249 L/h was comparable to the estimates obtained in similarly designed studies. Non-compartmental analysis with a 5-day continuous infusion estimated the CL 5FU to be 257 L/h [42], while an estimate of 270 L/h was reported for a 3-day continuous infusion [43]. Population pharmacokinetic analysis performed by Etienne et al presented an estimate of 235 L/h, where the data were described by a one-compartment model with first-order elimination [7].…”
Section: Discussionmentioning
confidence: 99%
“…CL 5FU of 249 L/h was comparable to the estimates obtained in similarly designed studies. Non-compartmental analysis with a 5-day continuous infusion estimated the CL 5FU to be 257 L/h [42], while an estimate of 270 L/h was reported for a 3-day continuous infusion [43]. Population pharmacokinetic analysis performed by Etienne et al presented an estimate of 235 L/h, where the data were described by a one-compartment model with first-order elimination [7].…”
Section: Discussionmentioning
confidence: 99%
“…25 Likewise, as our study reflects, other authors did not found a significant influence of hepatic function tests on predicting 5-FU Cl. 27 Plasma clearance of 5-FU is rate limited on the catabolic pathway by the activity of the dihydropyrimidine dehydrogenase (DPD). 28 It is now well recognized that decrease DPD enzyme activity can predispose cancer patients to severe life-threatening toxicity following treatment with routine doses of 5-FU.…”
Section: Discussionmentioning
confidence: 99%
“…5-FU clearance is highly variable and several factors contributing to its variability have been reported. Polymorphism in the gene coding for DPD (DPYD) has already been addressed and has been extensively discussed elsewhere [5,25] but age, gender, disease state and organ dysfunction (particularly liver failure) have also been reported to have an impact on 5-FU pharmacokinetics [26] [27,28]. Absence of correlation between body surface area and 5-FU clearance has been extensively demonstrated [29], [13].…”
Section: Metabolism and Excretion: (Figure 1)mentioning
confidence: 99%